Effects of Furnace Slope and Rotational Speed on the Carbothermic Reduction of Celestite in a Laboratory-Scale Rotary Kiln Furnace - Sezer, Rasit; Bilen, Aysegul; Hizli, Goksel; Erturk, Selim; Arslan, Cuneyt (SPRINGER HEIDELBERG, 2020)
The carbothermic reduction of celestite is the first step in producing many strontium products. The way materials move in the rotary kiln has an essential effect on the carbothermic reduction efficiency as well as the temperature. In this study, the reduction of celestite ore and excess carbon blend in a laboratory-scale rotary kiln was investigated. In the experiments carried out at three different temperatures, the rotational speed and slope of the furnace tube were altered, and their effects on the reaction efficiency were examined. The leachability of the reduced powders and the content of the unburned coke indicated the optimal parameters for the reaction. When the speed was increased to 10 rpm, the powders were more mobile in the stack and could react more easily with the furnace atmosphere. According to the results, celestite can be reduced by carbon at temperatures of 1000-1200 degrees C, at rates of between 5% and 75%. The maximum reaction yield (75%) was obtained with a slope of 2 degrees and a rotational speed of 6 rpm at 1100 degrees C.
Keywords: Celestite; Carbothermic reduction; Rotary kiln; Strontium sulfide; SRSO4; SRCO3; CONVERSION; CARBONATE; KINETICS; PRECIPITATION; (NH4)(2)SO4; WATER; Metallurgy & Metallurgical Engineering; Mining & Mineral Processing